Electron Beam-Assisted Synthesis of YAG:Ce Ceramics - Karipbayev, Zhakyp T.; Lisitsyn, Victor M.; Golkovski, Mikhail G.; Zhilgildinov, Zhassulan S.; Popov, Anatoli I.; Zhunusbekov, Amangeldy M.; Polisadova, Elena; Tulegenova, Aida; Mussakhanov, Dossymkhan A.; Alpyssova, Gulnur; Piskunov, Sergei (MDPI, 2023)
In this work, we present the results of the structure and luminescence properties of YAG:Ce (Y3Al5O12 doped with Ce3+ ions) ceramic samples. Their synthesis was carried out by sintering samples from the initial oxide powders under the powerful action of a high-energy electron beam with an energy of 1.4 MeV and a power density of 22–25 kW/cm2. The measured diffraction patterns of the synthesized ceramics are in good agreement with the standard for YAG. Luminescence characteristics at stationary/time-resolved regimes were studied. It is shown that under the influence of a high-power electron beam on a mixture of powders, it is possible to synthesize YAG:Ce luminescent ceramics with characteristics close to the well-known YAG:Ce phosphor ceramics obtained by traditional methods of solid-state synthesis. Thus, it has been demonstrated that the technology of radiation synthesis of luminescent ceramics is very promising. © 2023 by the authors. --//-- Karipbayev Z.T., Lisitsyn V.M., Golkovski M.G., Zhilgildinov Z.S., Popov A.I., Zhunusbekov A.M., Polisadova E., Tulegenova A., Mussakhanov D.A., Alpyssova G., Piskunov S.; Electron Beam-Assisted Synthesis of YAG:Ce Ceramics; (2023) Materials, 16 (11), art. no. 4102; DOI: 10.3390/ma16114102; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85161490971&doi=10.3390%2fma16114102&partnerID=40&md5=e33da4c2d44c563881bdeffe410d734b published under the CC BY 4.0 licence.
The work was carried out within the framework of the grant AP14870696 of the Ministry of Education and Science of the Republic of Kazakhstan. This research was funded by the Russian Science Foundation of the Russian Federation. (Grant No. 23-73-00108). A.I.P is also thankful for financial support from Latvian Project LZP-2018/1-0214. In addition, A.I.P. is thanking the Institute of Solid State Physics, University of Latvia (ISSP UL). ISSP UL as the Centre of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD01-2016-2017-Teaming Phase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; high-power electron flux; luminescence; structure; synthesis; YAG:Ce ceramics